Time-evolution of Heat Affected Zone (HAZ) of Friction Stir Welds of AA7075-T651 - Pastor, A. (2013)
Friction Stir Welding (FSW) is a novel solid-phase welding process, which has proved to have a great potential for the realization of welded joints in materials with poor weldability such as heat-treatable aluminum alloys. However, the thermal cycles generated during FSW change the mechanical properties in heat affected zone (HAZ) due to two effects: over-age and re-dissolution of hardening precipitates. In other hand, the re-dissolved precipitates produce a evolution of both the microstructure and mechanical properties due to the natural aging phenomenon. The aim of this paper was to analyze the microstructural evolution in the HAZ of FSW joints in AA7075-T651 alloy. For this purpose samples FSW welded butt plate 4 mm in thickness. On the welded joint microstructural characterization was performed by light microscopy (LM), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) and Vickers microhardness profiles (HV) after different elapsed times post welding. It was observed that the hardness increases with time after welding, due to the evolution of the phases present.